When Ground Shifts : the story of Dubai EXPO: creating hope in times of upheaval - Al-Hashimy, Reem (London: Profile Editions, 2025)
"When Ground Shifts is the extraordinary first-hand account of the United Arab Emirates' successful bid to host the first World Exposition ever to be held anywhere in the Middle East, South Asia or Africa. As the minister responsible and mother to a young family, the author Reem Al-Hashimy describes the international and personal challenges she faced leading a team which went on to stage one of the most unifying and ground-breaking international events of this century, for the first time providing an equal platform for participants of all nations. A story of resilience and ambition from the heart of Arabia, it challenges stereotypes and prejudices about the Middle East, offers an inspirational picture of what is possible for women and girls in the region and beyond, and sheds new light on a more hopeful vision for international relations at a time of global shifts and realignment. The book also offers the fascinating wider context of the Emirates and its role not only in large international events such as Expo and COP but also, in its rejection of the legacy of colonialism, as a trusted broker between nations and a leading country in the global south"
Keywords: Exhibitions -- United Arab Emirates - Dubai; EXPO (International Exhibitions Bureau) -- (2021 : UAE, Dubai)